خصائص وامتیازاتِ مصطفٰیﷺ : علامہ سعیدی کی شرح صحیح مسلم کا مطالعہ: Characteristics and Peculiarities of the Prophet: A Study of Allāma Saʻīdī's Sharḥ Ṣaḥīḥ Muslim (Al-Qamar, 2019)
The description of the characteristics of the Prophet (PBUH) has been an important topic in Sīra writings. Allāma Ghulām Rasūl Saʻīdī in his Sharḥ Ṣaḥīḥ Muslim has paid special attention to the mention of the characteristics and peculiarities of the Prophet. Highlighting the points regarding the characteristics of the Prophet he asserts that forgiveness of all the prophets is certain, but the promise of forgiveness in the world is only to the Prophet Muhammad. In spite of the account of forgiveness, the frequent worship of the Prophet was to encourage the Ummah to be thankful to Allah. The intercession of the Prophet is proved by Quran and Ḥadīth. To Saʻīdī, the use of word Badduʻā is not suitable in context of the Prophet instead the word duʻā-e-Zarar should be used. It concludes that the Prophet was a perfect man and unique in his personality and attributes.
Keywords: Prophet; Characteristics; Allāma Saʻīdī; Sharḥ Ṣaḥīḥ Muslim